Temparature Control In Oyester Mushroom Kumbung With Burlap As Cooler - Manunggal Ajie Putranto; Mad Yamin (PERTETA, 2012)
ABSTRACT A study was conducted in order to know the difference oyster mushroom yields given burlap and cooling treatment and with the one not given treatment. In this study using burlap as a coolant. Installation of pipe used to drain burlap sacks that are stored on the sidelines of the shelves, watering is done automatically using a timer every 15 minutes. After some time using treated burlap visible difference in temperature between the cooling rack using a burlap sack with a none. But the relative humidity is not too much different. Yields of both condition oyster mushroom with total 75 baglogs, the obtained total yield 23.5 kg treatment, while the total yield 16.7kg without treatment.[A1] Keywords: gunny sacks[A2] , temperature, yields, oyster mushroom